WADUL-E AS THE IMPLEMENTATION OF E-SERVICE IN THE NEW PUBLIC SERVICE PARADIGM - Afif Al Farizi; Dian Suluh Kusuma Dewi; Insyira Yusdiawan Azhar (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine how the application of the New Public Service concept to the WADUL-E Service (Aspiration and Electronic Complaints Forum) in Pacitan Regency. This study used a qualitative approach and the determination of informants using the purposive sampling technique. The results showed that the concept of the New Public Service was not fully applicable to the Pacitan WADUL-E Service, because the researchers did not find data related to the 6th indicator, which is serving not directing which contains the position of the leader here, not as the owner but as a public servant or public servant. However, the rest of the concept of the new public service is in accordance with the real situation in the Pacitan Wadule Service. Hence, it is necessary to have in-depth research to find out the leadership side in the service. Based this research, it can be conculed that it is one of the public innovation efforts created by the Pacitan Regency Government is to provide Complaint Services in the form of WADUL-E Services of Pacitan Regency which was formed and inaugurated on March 14, 2018. By utilizing this service, it is hoped that the aspirations and complaints of the Pacitan citizens are connected to regional government. Keywords: E-Service, New Public Service, WADUL-E Pacitan